Legal and secondary biopsychosocial outcomes of child sexual abuse: Experience from a hospital-based multidisciplinary child protection unit in an urban lower-middle income country setting - Riza C. Lorenzana; Mariella Sugue-Castillo; Atty Carmela Andal-Castro; Bernadette J. Madrid (Child Protection and Practice)
Background: Child sexual abuse (CSA) is prevalent in the Philippines. The Philippine General Hospital–Child Protection Unit (PGH-CPU) provides multidisciplinary management. Local literature on legal and secondary biopsychosocial outcomes of CSA is limited. Objective: Determine legal and biopsychosocial outcomes among CSA survivors and determine factors associated with reaching court and perpetrator conviction. Participants: CSA survivors evaluated at the PGH-CPU in 2009–2013. Methods: A mixed transdisciplinary design to obtain data from medical records, court documents, and interviews of study participants and key informants. Results: Factors associated with CSA cases reaching court were having multiple perpetrators (OR 5.26, 95% CI 1.45–19.05, p = 0.011) and an age difference of more than 10 years between child and perpetrator (OR 2.51, 95% CI 1.26–5.01, p = 0.009). A 10-year age difference between child and perpetrator was a significant determinant for conviction (OR 3.69, 95% CI 1.04–13.14, p = 0.044). Interviews showed that the child's testimony is the most significant factor for successful prosecution. CSA survivors have increased risks for negative biopsychosocial outcomes. Children who followed-up at PGH-CPU showed a significantly lower rate of suicide attempts (0% vs. 7.7% in children without follow-up, p = 0.023) and had lower odds of having multiple sexual partners (OR 0.12, 95% CI 0.03–0.49, p = 0.003) and being employed (OR 0.23, 95% CI 0.07–069, p = 0.009). Conclusions: There is a need to strengthen capacities of professionals to optimize legal processes and outcomes. CSA survivors have varied long-term outcomes requiring continued holistic aftercare interventions.